45 lat „Acta Universitatis Lodziensis Folia Archaeologica” - Andrzejewski, Aleksander (Acta Universitatis Lodziensis. Folia Archaeologica, 2025)
RECEIVED 31.07.2025 • VERIFIED 03.08.2025 • ACCEPTED 03.08.2025 Funding Information: University of Lodz Conflicts of interests: None Ethical Considerations: The Authors assure of no violations of publication ethics and take full responsibility for the content of the publication. The percentage share of the author in the preparation of the work is: A.A. 100% Declaration regarding the use of GAI tools: not used